AB1109 The Relationship between Disease Activity, Disease Duration, Patient Global Assessment, and Physical Function in Rheumatoid Arthritis. (10th June 2014) - Watanabe, T.; Kojima, T.; Takahashi, N.; Funahashi, K.; Hanabayashi, M.; Hirabara, S.; Asai, S.; Ishiguro, N.
Abstract : Background: With the advent of methotrexate and biological disease-modifying antirheumatic drugs, clinical remission has been a realistic goal in rheumatoid arthritis (RA). In 2011 ACR/EULAR Boolean-based definition of remission in RA, patient global assessment (PGA) is often the limiting factor for reaching remission. 1 The main determinants for the PGA are pain, function, and number of swollen joints. 2 Physical function will affair clinical remission. Given the tight correlation between physical function and loss of social and economic opportunities, 3 as well as clinical remission, functional remission is also an important goal. Objectives: To clarify the characteristics of Health Assessment Questionnaire (HAQ) and its items from the point of view of disease activity and disease duration of RA. Methods: 512 RA patients at Nagoya University Hospital were enrolled in this study. Physical function was assessed using HAQ, disease activity DAS28-CRP, PGA 0-10 visual analog scale. Pearson correlation coefficient, chi square test, and unpaired t-test were used for static analysis. Results: Patients were primarily women (81.4%). Mean age was 60.3±14.0 years, disease duration 13.0±10.4 years, HAQ-DI 0.67±0.75, and DAS28-CRP 2.37±1.02. HAQ-DI was getting worse in correlation with disease activity (r=0.452) (Fig. 1 ), and disease duration (r=0.446) (Fig. 2 ). In the early stage of RA (duration <2 years), HAQ-DI was strongly correlated with DAS28-CRP (r=0.758). Considering the questionnaires by, #10 Hygiene, #17 Grip, and #20 Activities had stronger correlation with disease activity. #1 Dressing & Grooming, #5 Eating, and #7 Eating had stronger correlation with disease duration. PGA had a most strong correlation with the HAQ-DI in the components of the DAS28-CRP (r=0.395). Of the patients who are in functional remission (HAQ-DI <0.5), 50.3% fulfilled PGA 0 or 1, of the patients whose HQA-DI ≥0.5, only 16.0% fulfilled PGA 0 or 1 (Fig. 3 ). 128 patients fulfilled Boolean-based remission, and 149 patients fulfilled three of four Boolean criteria except PGA. Mean HAQ-DI was the former 0.19, the latter 0.67, which showed a significant difference (Fig. 4 ). Conclusions: Physical function was associated with disease activity, especially in the early stage. In order to prevent the progression of dysfunction or to achieve functional remission, reducing disease activity is important. Some questionnaires correlated stronger with disease duration rather than disease activity, which suggests that reducing only disease activity is not enough. In addition, HAQ-DI is also associated with PGA. This study suggests that improving HAQ-DI by such as surgery and rehabilitation, leads to not only functional remission but also clinical remission through improving PGA. References: Studenic P, Smolen JS, Aletaha D. Near Misses of ACR/EULAR criteria for remission: effects of patient global assessment in Boolean an index-based definitions. Ann Rheum Dis 2012;71:1702-1705 Studenic P, Radnner H, Smolen JS, Aletaha D. Discrepancies between patients and physicians in their perceptions of rheumatoid disease activity. Arthritis Rheum 2012;64:2814-2823 Strand V, Khanna D. The impact of rheumatoid arthritis and treatment on patients' lifes. Clin Exp Rheumatol 2010;28:S32-40 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2079